KAJIAN KARAKTERISTIK DAS TUNTANG DAN MODEL PENGELOLAAN DAS TERPADU - Sriyana Sriyana (Diponegoro University, 2011)
A low carrying capacity of drainage basin or watershed may cause several problems, where floods occur inrainy season and droughts occur in dry season, also the occurrence of erosion, sedimentation and so on, hasbeen government’s problem in watershed management all along. In order to anticipate this condition,characteristic data of a watershed are required, so that it can be used as basic reference of watershedmanagement.The purpose of this paper is to conduct a study on the characteristics of Tuntang watershed of Central JavaProvince and watershed management model.The method of approach uses aspects of watershed geomorphology such as the shape of watershed, elongationratio and circularity ratio approaches, order of river using Strahle method, watershed density using Lynsleyformula, and river gradient calculated based on the comparison between elevation difference and length of mainrivers.Results show that magnitude index of Tuntang Sub watershed has elongated shape with Rc value between 0.27 to0.46, which means that the longer concentration time needed, the lower flood fluctuation. And relatively roundedshape with Rc value between 0.57 to 1.00, which means that the shorter concentration time needed, the higherflood fluctuation occurs. Sub watershed order range from 4 to 6 order, which means that river basins have floodwater level increase (moderately quick to fast), likewise water level decrease. Level slope between 0 - 8 % (lowflow velocity) with an area of 117605.56 Ha, and very steep slope > 40 % (very high flow velocity) with an areaof 4219.09 Ha. The highest drainage density occurs in Sub watershed of Tuntang downstream 1.88 Km / Km²,and lowest Sub watershed of Blorong 1.01 Km / Km². Based on both magnitudes, the water being stored is inmedium category and floods and droughts occur. The flow pattern has the shape of rectangular dendritic anddendritic medium, showing that soil characteristics is limestone and shale. To obtain optimal performance resultof Tuntang watershed, integrated watershed management program is needed in watershed managementintegration by involving various associated parties.